The risk of asthma mortality with inhaled long acting β-agonists. Issue 995 (21st October 2008) - Wijesinghe, M; Perrin, K; Harwood, M; Weatherall, M; Beasley, R
Abstract : This article reviews the available evidence as to whether inhaled long acting β-agonists (LABA) increase the risk of asthma mortality and considers the implications for the use of this treatment in the management of asthma. Randomised controlled trials suggest that LABAs prescribed as monotherapy may increase the risk of asthma death in certain circumstances, such as the unsupervised "off-label" use without concomitant inhaled corticosteroid (ICS) treatment in patients with unstable asthma. However, there is also evidence that the use of LABAs in conjunction with ICS treatment in adult asthma as recommended in current guidelines is not associated with an increased risk of asthma mortality. The only way in which a prescriber can ensure that a patient with asthma takes LABA treatment in conjunction with ICS is through a combination ICS/LABA product, an approach which may have additional therapeutic advantages. We propose that in the management of asthma, a case can now be made to limit the availability of LABAs to combination LABA/ICS therapy.